Method for synergistically preparing vaterite by catalytic conversion of waste gypsum through CO2 microbubble reinforced particle electrode

Through the method of strengthening the particle electrode of CO2 microbubble to catalyze the conversion of waste gypsum, the problem of low efficiency and poor purity in the technology of solidifying and sequestering the CO2 calcium carbonate preparation is solved, and efficient and uniform preparation of vaterite is achieved, which improves the utilization of waste gypsum rate and crystal structure mass of calcium carbonate.

CN119263330APending Publication Date: 2025-01-07KUNMING UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411387363.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-01
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing waste gypsum curing and sequestering of CO2 calcium carbonate preparation has problems such as low carbon dioxide capture efficiency, low purity of calcium carbonate components, poor crystal form, uneven crystal size distribution and high cost.

Method used

The method of catalytic conversion of waste gypsum by strengthening the particle electrode with CO2 microbubble is adopted, including three steps: strengthening dissolution of waste gypsum and directional removal of impurities, co-categorized conversion of CO2 microbubble and directional regulation of vaterite crystals, through microelectric field and O3 microbubble Synergistically perform solid-liquid separation, and use the joint action of electric field and particle electrodes to control the formation of calcium carbonate and crystal size distribution.

Benefits of technology

The high-efficiency conversion of CO2 is achieved, the prepared vaterite has high purity and uniform particle size distribution, which significantly improves the utilization rate of waste gypsum and the crystal structure perfection of calcium carbonate, and reduces the treatment cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263330A_ABST
    Figure CN119263330A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synergistically preparing vaterite by catalytic conversion of waste gypsum with a CO2 microbubble reinforced particle electrode, the method comprises three steps of waste gypsum reinforced dissolution and directional removal of impurities, catalytic conversion with the CO2 microbubble reinforced particle electrode and directional regulation and control of vaterite crystallization, and the dissolution of the waste gypsum and the directional removal of the impurities are completed at the same time. A micro electric field is adopted to cooperate with O3 microbubbles to strengthen dissolution, and pure waste gypsum slurry is prepared through solid-liquid separation; the CO2 microbubble synergistic particle electrode catalytic conversion comprises the following steps: blowing CO2 microbubbles from a cathode region under the condition of an electric field, sealing and curing CO2, refluxing liquid in an anode region to a dissolving step of waste gypsum, and crystallizing liquid in the cathode region after CO2 curing by adopting an evaporation method to prepare vaterite; according to the method, high-efficiency conversion of CO2 is realized, and the prepared vaterite is relatively high in purity and uniform in particle size distribution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing vaterite by catalytic conversion of waste gypsum by CO2 microbubble-enhanced particle electrodes, and belongs to the field of high-value-added resource utilization of solid waste. Background Art

[0002] Waste gypsum is a typical industrial solid waste generated by the chemical industry, mainly including phosphogypsum from the phosphorus chemical industry, flue gas desulfurization gypsum from flue gas treatment, titanium gypsum from the titanium industry, and fluorinated gypsum from hydrofluoric acid preparation. With the impact of waste gypsum on the ecological environment, many experts and scholars have conducted a lot of research on its resource utilization, mainly including building materials, roadbed materials, filling, valuable element extraction, preparation of environmental functional materials, etc. However, due to the large amount of original accumulated waste gypsum and the large amount of production, the existing consumption cannot meet the demand, and the poor market acceptance and high cost have seriously restricted the resource treatment of waste gypsum.

[0003] In order to increase the added value of waste gypsum, many researchers have paid attention to the development of carbon sequestration technologies using waste gypsum based on the chemical composition of waste gypsum. Henan Fusifei Technology Co., Ltd. proposed a method for preparing nano-calcium carbonate by carbon fixation of industrial solid waste gypsum (CN202410321875.5), and Sumitomo Osaka Cement Co., Ltd. of Japan proposed a method for fixing carbon dioxide, a method for manufacturing calcium carbonate, and a method for utilizing waste gypsum board (CN202280064675.5), directly introducing CO2 gas into waste gypsum to prepare calcium carbonate. Santan (Anhui) Science and Technology Research Institute Co., Ltd. proposed a production method for continuously producing ammonium sulfate and calcium carbonate by mineralizing gypsum with carbon dioxide (CN202311454776.6). Although a large number of technologies related to the preparation of calcium carbonate by capturing carbon dioxide gas using waste gypsum have emerged, these technologies have the disadvantages of low carbon dioxide capture efficiency, low purity of the prepared calcium carbonate component, poor crystal form of calcium carbonate, uneven crystal size distribution, and high cost. Summary of the invention

[0004] Aiming at the shortcomings of the existing waste gypsum solidification and sealing CO2 preparation technology for calcium carbonate, in order to increase the utilization rate of waste gypsum, reduce the processing cost, and improve the perfection of the calcium carbonate crystal structure, the present invention provides a method for preparing vaterite by catalytic conversion of waste gypsum by CO2 microbubbles, which mainly includes three key steps: waste gypsum enhanced dissolution and directional removal of impurities, CO2 microbubbles synergistic catalytic conversion of particle electrodes and directional regulation of vaterite crystallization. The dissolution of waste gypsum and directional removal of impurities are completed at the same stage, micro-electric field is used to coordinate O3 microbubbles to enhance dissolution, and the preparation of pure waste gypsum slurry is achieved by solid-liquid separation; CO2 microbubbles synergistic particle electrode catalytic conversion is carried out under electric field conditions, CO2 microbubbles are blown into the cathode area, CO2 is sealed and solidified under certain temperature conditions, the liquid in the anode area flows back to the dissolution step of waste gypsum, the liquid in the cathode area after CO2 solidification enters the directional regulation step of vaterite crystallization, vaterite is prepared by evaporation, the liquid part flows back to the dissolution step of waste gypsum, and the prepared vaterite is dried to obtain a finished product.

[0005] The specific steps of the method of the present invention are as follows:

[0006] 1. After mixing phosphogypsum with water at a solid-liquid ratio of 1:5 to 30, the mixture is subjected to the synergistic effect of micro-electric field and O3 micro-bubbles to achieve enhanced dissolution of waste gypsum, directional removal of impurities, and solid-liquid separation;

[0007] The waste gypsum includes one of titanium gypsum, flue gas desulfurization gypsum, fluorite and phosphogypsum;

[0008] The voltage of the micro-electric field is 0.1-6V, the electrode material is alloy, ruthenium-iridium-titanium, and the electrode distance is 10-30cm; the ozone content in the O3 microbubbles is 5%-20% (volume concentration), the flow rate is 0.5-1.5m / s, and the diameter of the microbubble outlet is 0.5mm-1.5mm; the coordinated treatment time of the micro-electric field and O3 microbubbles is 30-120min;

[0009] 2. The phosphogypsum slurry obtained after solid-liquid separation in step (1) is passed into a catalytic conversion device equipped with a granular electrode, wherein an anode and a cathode are arranged in the device, and CO2 microbubbles are blown into the cathode region at 45°C to 100°C under the action of an electric field to achieve CO2 solidification;

[0010] The CO2 content in the CO2 microbubbles is 2% to 60% (volume concentration), the particle electrode is one or more of washed vanadium-titanium magnet tailings, lead-zinc tailings, iron tailings, and copper tailings, and the anode or cathode is a plate-shaped electrode formed by pressing vanadium-titanium magnet tailings, lead-zinc tailings, iron tailings, and copper tailings at 300 to 600 MPa; the electric field voltage is 5V to 36V, and the electrode distance is 5 to 20cm; the CO2 microbubble flow rate is 0.1 to 0.8m / s, and the microbubble outlet diameter is 0.1mm to 1mm;

[0011] 3. Collect the liquid in the cathode area after CO2 solidification, and use evaporation method to crystallize it. After the crystals are dried, they become vaterite;

[0012] The temperature for preparing vaterite by the evaporation method is 50°C to 90°C, and the distilled water is condensed and recycled;

[0013] 4. The anode area liquid after CO2 solidification and the liquid evaporated and collected in step (3) are returned to step 1 for dissolution.

[0014] Main technical principles: Waste gypsum is slightly soluble, and its solubility is related to the activity of the aqueous solution. The micro-electric field cooperates with O3 microbubbles to enhance the dissolution and impurity removal of waste gypsum. O3 has a strong oxidizing effect and can oxidize the organic impurities in the waste gypsum system. Metal ion impurities are directed to migrate to the electrode surface under the action of the electric field to achieve removal. At the same time, the electrochemical electrolysis can increase the activity of the waste gypsum slurry, thereby enhancing the solubility of calcium and sulfate in the waste gypsum, and the insoluble and insoluble impurities are removed by solid-liquid separation; high-concentration calcium and sulfate ion solutions enter the CO2 microbubble-coordinated particle electrode catalytic conversion stage. Under electrochemical conditions, a large amount of hydroxide ions are generated in the cathode area. Under alkaline conditions, calcium ions react with CO2 dissolved in water to form calcium carbonate. The CO2 introduced from the bottom ensures the uniform generation of calcium carbonate, and the size and distribution of calcium carbonate crystals are controlled under the joint action of the electric field and the particle electrode.

[0015] Advantages and technical effects of the invention: The technology achieves high-efficiency conversion of CO2, and the prepared vaterite has high purity and uniform particle size distribution. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the process of preparing vaterite by catalytic conversion of waste gypsum by CO2 microbubble-enhanced granular electrode;

[0017] Figure 2 XRD (left) and SEM (right) images of vaterite produced for CO2 sequestration in flue gas desulfurization gypsum;

[0018] Figure 3 XRD (left) and SEM (right) images of vaterite produced for CO2 sequestration in titanium gypsum;

[0019] Figure 4 XRD (left) and SEM (right) images of vaterite produced for CO2 sequestration in phosphogypsum. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below by way of examples, but the protection scope of the present invention is not limited to the contents described above.

[0021] Example 1: Figure 1 As shown, the method for preparing vaterite by using CO2 microbubbles to enhance the catalytic conversion of flue gas desulfurization gypsum by granular electrode is as follows:

[0022] (1) Enhanced dissolution of flue gas desulfurization gypsum and directional removal of impurities

[0023] The flue gas desulfurization gypsum and water are mixed at a solid-liquid ratio of 1:5 to 30, and the mixture is passed into a dissolution and impurity removal device. A microbubble outlet is provided at the bottom of the device, and the outlet diameter is 0.5 to 1.5 mm. An anode and a cathode are arranged in the device, and the distance between the anode and the cathode is 10 to 30 cm. O3 microbubbles (ozone content is 5 to 20%, and the flow rate is 0.5 to 1.5 m / s) are introduced from the microbubble outlet. The mixture is treated for 30 to 120 minutes under the synergistic effect of a micro-electric field of 0.1 to 6 V and O3 microbubbles. After the treatment, the solid and liquid are separated;

[0024] (2) CO2 microbubbles synergistic with particle electrodes for catalytic conversion

[0025] The liquid obtained after the solid-liquid separation in step (1) is passed into a catalytic conversion device, wherein an anode and a cathode (a plate-shaped electrode formed by pressing vanadium-titanium magnet tailings or iron tailings at 300 MPa) are arranged in the device, the distance between the anode and the cathode is 5 to 20 cm, the device is filled with a granular electrode, the granular electrode is selected from washed vanadium-titanium magnet tailings, lead-zinc tailings, and copper tailings, a microbubble outlet is opened at the bottom of the cathode region of the device, the microbubble outlet caliber is 0.1 mm to 1 mm, CO2 microbubbles (flow rate is 0.1 to 0.8 m / s, CO2 content is 2% to 60%) are passed through the microbubble outlet, and CO2 solidification and catalytic conversion are achieved at an electric field voltage of 5 V to 36 V and 45° C. to 100° C.;

[0026] (3) Directional control of vaterite crystallization

[0027] The liquid in the anode region of the catalytic converter in step (2) is discharged, evaporated and crystallized at 50° C. to 90° C., and the crystallized product is dried to obtain the vaterite product;

[0028] The specific parameters of the experimental group are shown in Table 1. At the same time, an experimental control group was set up, using graphite as the particle electrode or electrode material; the above experimental results are shown in Table 2;

[0029] Table 1

[0030]

[0031] Table 2

[0032] Group Group 1 Group 2 Group 3 contrast <![CDATA[CO2 conversion rate]]> 92% 95% 94% 80% Purity of finished product 95% 98% 97% 70%

[0033] Through the test of the inlet and outlet CO2 content and the analysis of the prepared vaterite content, the CO2 conversion efficiency of the method of the present invention is greater than 90%, and the purity of the prepared vaterite is greater than or equal to 95%; the electrode material prepared from solid waste has a significant effect on improving the CO2 conversion efficiency and the purity of vaterite. The microscopic crystal morphology and mineral composition of the prepared vaterite are as follows: Figure 2 As shown, its crystal morphology is regular spherical, evenly distributed and highly crystallized.

[0034] Example 2: The method for preparing vaterite by using CO2 microbubbles to enhance the catalytic conversion of titanium gypsum with granular electrodes is as follows:

[0035] (1) Enhanced dissolution of titanium gypsum and directional removal of impurities

[0036] Titanium gypsum and water are mixed at a solid-liquid ratio of 1:5 to 30 in g:mL, and the mixture is passed into a dissolution and impurity removal device, a microbubble outlet is provided at the bottom of the device, and the outlet diameter is 0.5 to 1.5 mm. An anode and a cathode are arranged in the device, and the distance between the anode and the cathode is 10 to 30 cm. O3 microbubbles (ozone content is 5 to 20%, and the flow rate is 0.5 to 1.5 m / s) are introduced from the microbubble outlet, and the mixture is treated for 30 to 120 minutes under the synergistic effect of a micro-electric field of 0.1 to 6 V and O3 microbubbles, and solid-liquid separation is performed after the treatment is completed;

[0037] (2) CO2 microbubbles synergistic with particle electrodes for catalytic conversion

[0038] The liquid obtained after the solid-liquid separation in step (1) is passed into a catalytic conversion device, wherein an anode and a cathode (a plate-shaped electrode formed by pressing vanadium-titanium magnet tailings, lead-zinc tailings or iron tailings at 600 MPa) are arranged in the device, the distance between the anode and the cathode is 5 to 20 cm, the device is filled with a granular electrode, the granular electrode is selected from washed iron tailings, lead-zinc tailings and copper tailings, a microbubble outlet is opened at the bottom of the cathode region of the device, the microbubble outlet caliber is 0.1 mm to 1 mm, CO2 microbubbles (flow rate is 0.1 to 0.8 m / s, CO2 content is 2% to 60%) are passed through the microbubble outlet, and CO2 solidification and catalytic conversion are achieved at an electric field voltage of 5 V to 36 V and 45° C. to 100° C.;

[0039] (3) Directional control of vaterite crystallization

[0040] The liquid in the anode region of the catalytic converter in step (2) is discharged, evaporated and crystallized at 50° C. to 90° C., and the crystallized product is dried to obtain the vaterite product;

[0041] The specific parameters of the experimental group are shown in Table 3. At the same time, an experimental control group was set up, using graphite as the particle electrode or electrode material; the above experimental results are shown in Table 4;

[0042] Table 3

[0043]

[0044] Table 4

[0045] Group Group 1 Group 2 Group 3 contrast <![CDATA[CO2 conversion rate]]> 93% 96% 93% 79% Purity of finished product 96% 98% 97% 71%

[0046] Through the test of the inlet and outlet CO2 content and the analysis of the prepared vaterite content, the CO2 conversion efficiency of this method is greater than 90%, and the purity of the prepared vaterite is greater than 96%; the electrode material prepared from solid waste has a significant effect on improving the CO2 conversion efficiency and the purity of vaterite. The microscopic crystal morphology and mineral composition of the prepared vaterite are as follows Figure 3 As shown, its crystal morphology is regular spherical, evenly distributed and highly crystallized.

[0047] Example 3: The method for preparing vaterite by using CO2 microbubbles to enhance the catalytic conversion of phosphogypsum with granular electrodes is as follows:

[0048] (1) Enhanced dissolution of phosphogypsum and directional removal of impurities

[0049] The phosphogypsum and water are mixed at a solid-liquid ratio of 1:5 to 30 in g:mL, and the mixture is passed into a dissolution and impurity removal device, a microbubble outlet is provided at the bottom of the device, and the outlet diameter is 0.5 to 1.5 mm. An anode and a cathode are arranged in the device, and the distance between the anode and the cathode is 10 to 30 cm. O3 microbubbles (ozone content is 5 to 20%, and the flow rate is 0.5 to 1.5 m / s) are passed from the microbubble outlet, and the mixture is treated for 30 to 120 minutes under the synergistic effect of a micro-electric field of 0.1 to 6 V and O3 microbubbles, and solid-liquid separation is performed after the treatment is completed;

[0050] (2) CO2 microbubbles synergistic with particle electrodes for catalytic conversion

[0051] The liquid obtained after the solid-liquid separation in step (1) is passed into a catalytic conversion device, wherein an anode and a cathode (a plate-shaped electrode formed by pressing vanadium-titanium magnet tailings or iron tailings at 500 MPa) are arranged in the device, the distance between the anode and the cathode is 5 to 20 cm, the device is filled with a granular electrode, the granular electrode is selected from washed vanadium-titanium magnet tailings, lead-zinc tailings, and copper tailings, a microbubble outlet is opened at the bottom of the cathode region of the device, the microbubble outlet caliber is 0.1 mm to 1 mm, CO2 microbubbles (flow rate is 0.1 to 0.8 m / s, CO2 content is 2% to 60%) are passed through the microbubble outlet, and CO2 solidification and catalytic conversion are achieved at an electric field voltage of 5 V to 36 V and 45° C. to 100° C.;

[0052] (3) Directional control of vaterite crystallization

[0053] The liquid in the anode region of the catalytic converter in step (2) is discharged, evaporated and crystallized at 50° C. to 90° C., and the crystallized product is dried to obtain the vaterite product;

[0054] The specific parameters of the experimental group are shown in Table 5. At the same time, an experimental control group was set up, using graphite as the particle electrode or electrode material; the above experimental results are shown in Table 6;

[0055] Table 5

[0056]

[0057] Table 6

[0058] Group Group 1 Group 2 Group 3 contrast <![CDATA[CO2 conversion rate]]> 85% 95% 90% 74% Purity of finished product 90% 94% 89% 75%

[0059] Through the test of the inlet and outlet CO2 content and the analysis of the prepared vaterite content, the CO2 conversion efficiency of the method of the present invention is greater than 85%, and the purity of the prepared vaterite is greater than 89%; the electrode material prepared from solid waste has a significant effect on improving the CO2 conversion efficiency and the purity of vaterite. The microscopic crystal morphology and mineral composition of the prepared vaterite are as follows Figure 4 As shown, its crystal morphology is regular spherical, evenly distributed and highly crystallized.

Claims

1. A method for preparing vaterite by catalytic conversion of waste gypsum by CO2 microbubble-enhanced granular electrode, characterized in that: Here are the steps: (1) After phosphogypsum is mixed with water, the mixture is subjected to the synergistic effect of a micro-electric field and O3 microbubbles to achieve enhanced dissolution of waste gypsum, directional removal of impurities, and solid-liquid separation; (2) passing the phosphogypsum slurry obtained after solid-liquid separation in step (1) into a catalytic converter equipped with a granular electrode, and simultaneously blowing CO2 microbubbles into the cathode region to achieve CO2 solidification under the action of an electric field at 45°C to 100°C; (3) Collecting the liquid in the cathode region after CO2 solidification, using evaporation method to crystallize, and the crystals after drying are vaterite; (4) The liquid in the anode region after CO2 solidification and the liquid collected by evaporation in step (3) are both returned to step (1) for dissolution.

2. The method for preparing vaterite by catalytic conversion of waste gypsum by CO2 microbubble-enhanced granular electrode according to claim 1, characterized in that: The waste gypsum includes one of titanium gypsum, flue gas desulfurization gypsum, fluorine gypsum and phosphogypsum, and the solid-liquid ratio (g:mL) of the waste gypsum and water is 1:5-30.

3. The method for preparing vaterite by catalytic conversion of waste gypsum by CO2 microbubble-enhanced granular electrode according to claim 1, characterized in that: The voltage of the micro-electric field is 0.1-6V, and the electrode material is alloy, ruthenium, iridium and titanium; the ozone content in the O3 micro-bubbles is 5%-20%, the flow rate is 0.5-1.5m / s, and the diameter of the micro-bubble outlet is 0.5mm-1.5mm.

4. The method for preparing vaterite by catalytic conversion of waste gypsum by CO2 microbubble-enhanced granular electrode according to claim 1, characterized in that: In step (2), the CO2 content is 2% to 60%, the particle electrode is one or more of the washed vanadium-titanium magnet tailings, lead-zinc tailings, iron tailings, and copper tailings, and the anode or cathode is a plate electrode formed by pressing the titanium magnet tailings, lead-zinc tailings, iron tailings, and copper tailings at 300 to 600 MPa; the electric field voltage is 5V to 36V; the CO2 microbubble flow rate is 0.1 to 0.8m / s, and the microbubble outlet diameter is 0.1mm to 1mm.

5. The method for preparing vaterite by catalytic conversion of waste gypsum by CO2 microbubble-enhanced granular electrode according to claim 1, characterized in that: The evaporation crystallization temperature is 50℃~90℃.

Citation Information

Patent Citations

  • Production method of device for continuously producing ammonium sulfate and calcium carbonate by using carbon dioxide mineralized gypsum

    CN117482735A

  • Method for immobilizing carbon dioxide, method for producing calcium carbonate, and method for utilizing waste gypsum board

    CN118019713A

  • Method for preparing nano calcium carbonate through industrial solid waste gypsum carbon sequestration

    CN118343817A